Alzheimer's disease—one clinical syndrome, two radiological expressions: a study on blood pressure. Issue 9 (16th August 2004) - de Leeuw, F-E; Barkhof, F; Scheltens, P
Abstract : Background: Vascular risk factors could play a role in the aetiology of Alzheimer's disease, but this has not been investigated in relation to neuroimaging findings Objective: To evaluate the distribution of blood pressure and an indicator of atherosclerosis (pulse pressure) in patients with Alzheimer's disease with and without small vessel disease. Methods: 152 Alzheimer patients underwent 1.0T MRI scanning. Blood pressure was measured with a sphygmomanometer. Small vessel disease was assessed by the presence of lacunar infarcts and white matter lesions. The distribution of blood pressure and pulse pressure, with or without small vessel disease, was assessed by linear regression analysis. Results: Patients with small vessel disease had a higher blood pressure, a wider pulse pressure, and an increased prevalence of hypertension. These findings were strongly age dependent: for patients under 65, mean systolic blood pressure was higher in the subpopulation with small vessel disease than in those without (mean (SD): 149.9 (19.3) v 135.7 (20.5) mm Hg; p = 0.02). Hypertension was more common in patients with white matter lesions than in those without (75.6% v 45.1%; p = 0.03) and the pulse pressure was higher (61.9 (14.4) v 51.7 (11.5) mm Hg; p = 0.01). There was no relation between blood pressure and the degree of (sub)cortical and hippocampal atrophy in patients without small vessel disease. Conclusions: There was heterogeneity in Alzheimer's disease patients with respect to blood pressure and pulse pressure. Alzheimer's disease encompasses a heterogeneous group of disorders which share a common cognitive profile but with distinct radiological features with respect to white matter lesions.